Vanishing White Matter Disease: A Case Report - Islam, Mohammad Imnul; Hoque, Skazimul; Islam, Md Tariqul; Saha, Narayan Chandra; Matin, Abdul; Rahman, AKM Matiur; Saleh, Abu Sadat Md (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v35i3.10526 Bangladesh J Child Health 2011; Vol 35 (3): 127-129